Z prawnej problematyki zakładania i prowadzenia działalności przez spółdzielcze grupy producentów rolnych - Suchoń, Aneta (Wydawnictwo Naukowe UAM, 2012)
The aim of the paper was to identify the legal aspects of establishing and carrying out economic activity by cooperative groups of agricultural producers. Although there have been attempts to simplify the process of establishing and running agricultural business (amendments to the existing law on groups of agricultural producers and the provisions of cooperative law), there are still a number of provisions that raise doubts as to their interpretation. To help maintain durable structures, it would certainly be recommendable to oblige groups to carry out economic activity for at least 10 years as well as to prolong the required minimum period of belonging to an agricultural producers group. The possibility of passing a resolution allowing to liquidate a group of agricultural producers after the EU funds have been utilised does not encourage creation and maintenance of strong, competitive groups. Further development of agricultural producers groups in Poland requires continued financial support from the European Union going also after 2013. The EU funds should go to new groups of producers as well as those already operating in the market, and the scale of assistance should depend not only on the income of the agricultural producers group, but also the number of their members.

Lo scopo dell’articolo è di indicare i problemi giuridici legati alla costituzione e svolgimento dell’attività da parte delle aggregazioni delle cooperative produttori agricoli e di tentare di risorverli. Concludendo, l’autrice afferma tra l’altro che il legislatore cerca di semplificare le regole di costituzione e funzionamento delle aggregazioni delle cooperative produttori agricoli, introducendo modifiche alle leggi sulle aggregazioni dei produttori agricoli e alla legge del Diritto delle cooperative. Tuttavia molte norme destano tuttora dubbi. Al fine di creare strutture stabili sarebbe indubbiamente auspicabile imporre alle aggregazioni di svolgere l’attività per un periodo minimio, p.es. 10 anni, e prolungare il tempo obbligatorio durante il quale i produttori agricoli devono rimanere aggregati. La possibilità di approvare la deliberazione di scioglimento dopo aver usufruito dei fondi dell’Ue non favorisce la costituzione dei soggetti forti e competitivi. Per un ulteriore sviluppo delle aggregazioni dei produttori agricoli in Polonia è indispensabile che l’Unione europea continui ad offrire il sostegno economico dopo il 2013. Al tempo stesso a poterne beneficiare dovrebbero essere sia i soggetti emergenti sia quelli già presenti sul mercato. Inoltre, l’ammontare dell’aiuto non dovrebbe dipendere esclusivamente dal reddito delle aggregazioni dei produttori agricoli, ma anche dal numero dei soci.
THE LEGAL ISSUES OF ESTABLISHING AND CARRYING ECONOMIC ACTIVITY BY COOPERATIVE GROUPS OF AGRICULTURAL PRODUCERS
DELLE QUESTIONI GIURIDICHE DI COSTITUZIONE E SVOLGIMENTO DELL’ATTIVITÀ DA PARTE DELLE AGGREGAZIONI DELLE COOPERATIVE PRODUTTORI AGRICOLI